Interactive Design in LAMS: Pushing the Boundaries of Traditional Lecturing - Dobozy, Eva (University of Nicosia Press, 2011)
This paper explores the utility of interactive lecture podcasting in LAMS and the impact of structured dialogue design. It reports how curriculum renewal and innovation were greeted with scepticism by teacher education students enrolled in a compulsory curriculum unit at an Australian university. An analytic induction methodology in conjunction with educational data mining techniques was used to analyse the data. The purpose of the study was to understand one aspect of students' active participatory learning behaviour deemed vital for their success in higher education (HE): willingness to engage in online peer-to-peer dialogue. The paper closes with a recommendation for more systematic monitoring of HE students' online learning behaviour.